PERBEDAAN KINERJA KEUANGAN SEBELUM DAN SESUDAH PANDEMI COVID-19 PADA PERUSAHAAN SEKTOR KESEHATAN YANG TERDAFTAR DI BEI - Sara Intan Hartati; Ummi Kalsum; Belliwati Kosim (Universitas Nusa Cendana, 2022)
This study aims to determine whether or not there are differences in financial performance in the health sector (hospitals) listed on the Indonesia Stock Exchange during the Covid-19 pandemic. Comparative quantitative approach is the method used in this research. The type of data used is secondary data obtained from the Indonesia Stock Exchange in the form of financial statements of registered Health Sector Companies (Hospitals) and presenting financial report data on the Indonesia Stock Exchange Quarter 1 to 4 of 2019 as a reflection of conditions before the Covid-19 pandemic and reports financial year 2020 Quarters 1 to 4 as a reflection of conditions during the Covid-19 pandemic. The research variable used is the liquidity ratio proxied by (Current Ratio and Quick Ratio) Solvency ratio is proxied by (Debt to Equity Ratio and Debt to Total Assets) Activity ratio is proxied by (Fixed Assets Turn Over and Total Assets Turn Over), Profitability ratios are proxied with (Return On Equity Ratio and Net Profit Margin). The results of this study indicate that the variables of liquidity, solvency, activity have no difference in financial performance while the profitability variable shows there is a difference in financial performance. Keywords: Financial Performance, Liquidity Ratio, Profitability Ratio